Ultrasound Guided Versus CT-Controlled Pararadicular Injections in the Lumbar Spine: A Prospective Randomized Clinical Trial - Loizides, A.; Gruber, H.; Peer, S.; Galiano, K.; Bale, R.; Obernauer, J. (American Journal of Neuroradiology, 2013)
BACKGROUND AND PURPOSE: Injection therapies play a major role in the treatment of lower back pain and are to date performed mainly under CT- or fluoroscopic guidance. We conducted this study to evaluate the accuracy, time savings, radiation doses, and pain relief of US-guided pararadicular injections versus CT-controlled interventions in the lumbar spine in a prospective randomized clinical trial. MATERIALS AND METHODS: Forty adult patients were consecutively enrolled and assigned to a US or CT group. US-guided pararadicular injections were performed on a standard US device by using a broadband curved-array transducer (9–4 or 5–1 MHz). In the in-plane technique, the needle was advanced through the respective segmental intertransverse ligament. The needle tip position was verified by CT. The CT-guided approaches were performed under standardized procedures by using the CT-positioning laser function. RESULTS: The accuracy of US-guided interventions was 90%. The mean time to final needle placement in the US group was 4.0 ± 1.8 minutes, and in the CT group, 7.6 ± 2.1 minutes. The mean radiation doses, including CT confirmation for study purposes only, were 20.3 ± 9.0 mGy cm for the US group and 42.6 ± 36.1 mGy cm for the CT group. Both groups showed the same significant pain relief (P < .05) without relevant “intermethodic” differences of pain relief (P > .05). CONCLUSIONS: US-guided pararadicular injections show a therapeutic effect similar to that in the time-consuming, expensive, ionizing CT or fluoroscopically guided pararadicular injections and result in a significant reduction of procedure time expenditure and avoidance of radiation. PAPpararadicular aditus planeUSultrasoundVASVisual Analog Scale